Alkaloids and diarylheptanoids of hippobroma longiflora and pellacalyx saccardianus: structure and bioactivity - Chan, Zi-Yang (2021)
Plant secondary metabolites such as alkaloids and diarylheptanoids play a crucial role in drug discovery due to their high structural diversity and useful biological activity. The present research aims to isolate and elucidate bioactive alkaloids and/or diarylheptanoids from two understudied Malaysian angiosperms, i.e., Hippobroma longiflora (L.). G. Don. (Campanulaceae) and Pellacalyx saccardianus Scort. (Rhizophoraceae). H. longiflora is a naturalised herb with ethnobotany suggestive of neuroactive alkaloids, while P. saccardianus is a rainforest tree that exhibited remarkable cytotoxic activity.